KESELAMATAN BERLALU LINTAS DI KOTA BOGOR - Kurniati, Ni Luh Wayan Rita; Setiawan, Indra; Sihombing, Sarinah (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2017)
The purpose of this study is to analyze the influence of rider discipline, motor condition and road, on traffic safety. This research is a quantitative research using path analysis method. The population of this study were 42,625 riders of KS Tubun and Tajur roads. The sample is 684 riders with sample technique using incidental sampling. The results showthat traffic safety (X3) is strongly influenced by motorist discipline (X1) and Motor and Road conditions (X2). Safety in traffic will increase if the means of traffic infrastructure,Motor and Road conditions are function properly asthe vehicle equipments, traffic signs,markers, road user safety equipment, road conditions, and other traffic support facilities